Zooplankton composition and structure in the Indus River Estuary, Sindh, Pakistan - Mushaiyada Mairaj; Sher khan Panhwar; Fatima Hayat Shaheen Zafar (مجلة بغداد للعلوم)
In this study abundance and composition of zooplanktons in the Indus River Estuary was conducted to examine habitat characteristics and its impact on tiny organisms. Overall 30,656 individuals were identified and segregated into seven major groups including Copepods, Cnidarians, Decapods, Mollusk, Pisces, Amphipods and Chaetognaths. For better understanding they were further divided into eighteen planktonic categories. Among them Lucifer spp. comprises of 52.21% was the most abundant group with a peak appeared in March whereas Chaetognaths were rarely observed in the entire study period. Species diversity exhibited a mixed trend with the highest values (0.776) of dominance observed in spring (March). The results of Canonical Correspondence Analysis (CCA) indicate (60.2% and 39.79%) variability among first II axis. On this basis of the result it is obvious that water turbidity is trigger of the abundance and distribution whereas total dissolved solids (TDS) showed minimal influence deduced from CCA analysis.